STUDI PEMECAHAN MASALAH DALAM PEMBELAJARAN FISIKA: TINJAUAN SISTEMATIS - Kiraga, Festo (EduFisika: Jurnal Pendidikan Fisika, 2023)
This research is the first to conduct a systematic review of problem solving learning in physics learning. The research aims to synthesize the existing literature on the learning models and experimental methods that can improve high school students’ physics problem solving abilities. The method used in this research is qualitative research using a systematic literature review method. Data collection techniques by reviewing books, journals, literature, notes and various reports related to the problem you want to solve. Data samples were taken by tracing several scientific articles resulting from previous researchers’ research on developmental, experimental and descriptive research. The data analysis technique used is matrix synthesis. Based on the research that has been conducted, it was found that almost all articles apply learning models and use experimental methods to improve high school students’ physics problem solving abilities. The research contributes to the literature on physics education and problem solving by providing a comprehensive and systematic overview of the existing literature on problem solving learning in physics learning. The novelty of this research is that it introduces a new framework of problem solving learning in physics learning. The research also provides empirical evidence of the effectiveness and feasibility of problem solving learning in physics learning. Future research may conduct empirical studies to test the effectiveness and feasibility of problem solving learning in physics learning.